2020
DOI: 10.3390/su12093789
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Cadmium and Lead Accumulation and Transfer by Chenopodium Quinoa Will

Abstract: Potentially toxic elements are persistent in the environment and plants have the ability to absorb and transfer them from soil in edible parts. The objectives of this study were to characterize the distribution of Cd and Pb in quinoa tissues and to investigate their accumulation and transfer from irrigated water in edible parts of quinoa. For the purpose of this study experiment and simulated pollution in the form of different metal concentration in water that was used for irrigation was designed. Distribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 42 publications
0
10
0
2
Order By: Relevance
“…8 Consequently, the human health was threated by food contaminants due to both Cd and Pb. 7 The Pb and Cd content, respectively, was 34.77 mg kg À1 and 0.47 mg kg À1 in Chau Khe cra village, Tu Son town, Bac Ninh province, Vietnam. 9 Another report also indicated that the content of Pb and Cd in outdoor soil samples at Bui Village, Northern of Vietnam was 76.94 mg kg À1 and 0.35 mg kg À1 , respectively.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…8 Consequently, the human health was threated by food contaminants due to both Cd and Pb. 7 The Pb and Cd content, respectively, was 34.77 mg kg À1 and 0.47 mg kg À1 in Chau Khe cra village, Tu Son town, Bac Ninh province, Vietnam. 9 Another report also indicated that the content of Pb and Cd in outdoor soil samples at Bui Village, Northern of Vietnam was 76.94 mg kg À1 and 0.35 mg kg À1 , respectively.…”
Section: Introductionmentioning
confidence: 94%
“… 5 The Cd and Pb content of garden soil in Silesia Province southern Poland was <2.0–69.9 mg kg −1 and <20.0–2823.9 mg kg −1 , respectively. 6 In Vietnam, several areas have been also polluted by both Pb and Cd, such as heavy metal (Pb, Cd) pollution in agricultural soil in Dong Mai lead recycling craft village in Hung Yen province 7 and a suburban areas of Hanoi city. 8 Consequently, the human health was threated by food contaminants due to both Cd and Pb.…”
Section: Introductionmentioning
confidence: 99%
“…Results of Cd quantities in plant tissues also showed that marigold roots accumulated the highest content of Cd followed by stems and then leaves, respectively, which is consistent with a previous study 21 . This ornamental plant exhibited excluder potential, that is -the propensity to accumulate Cd in lower concentrations in above ground parts compared to roots 23 .…”
Section: Resultsmentioning
confidence: 97%
“…Marigold roots accumulated the highest Cd followed by stems and then leaves, respectively, which is consistent with a previous study 8 . This plant exhibited excluder potential, that is, the propensity to accumulate Cd in lower concentrations in above-ground parts compared to roots 26 . Previous research has indicated that compost-amended soils decreased Cd bioavailability by approximately 50% in the hyperaccumulator P .…”
Section: Resultsmentioning
confidence: 99%